An innovative approach to teaching high school students about indoor air quality. - Neumann CM; Bloomfield MM; Harding AK; Sherburne H (Journal of Environmental Health, 1999)
Since 1988, the Science and Math Investigative Learning Experiences (SMILE) Program at Oregon State University (OSU) has provided science and math enrichment to over 2,400 precollege minority and low-income school children in Oregon. In 1996, OSU received a four-year grant from the National Institute of Environmental Health Sciences (NIEHS) to improve teachers', students', and community members' understanding of environmental health science issues. This effort represents a collaboration of science educators from the SMILE program, environmental health scientists from OSU's Department of Public Health, and the OSU Environmental Health Sciences Center. Each year, a different environmental health science topic is highlighted. Topics have included household chemicals, water quality, indoor air quality, and food safety. The theme for the 1997-1998 school year was indoor air quality. Year-long educational activities associated with the NIEHS grant are curriculum development, teacher training workshops, and a variety of hands-on, after-school exercises for elementary, middle, and high school students. This paper describes an innovative approach used to help high school students develop critical thinking and real-world problem-solving skills while learning about indoor air quality.